2008
DOI: 10.3324/haematol.13441
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intensity conditioning allogeneic stem cell transplantation for Hodgkin's lymphoma: identification of prognostic factors predicting outcome

Abstract: BackgroundThe role of reduced intensity conditioning allogeneic stem transplantation (RICalloSCT) in the management of patients with Hodgkin's lymphoma remains controversial. Design and MethodsTo further define its role we have conducted a retrospective analysis of 285 patients with HL who underwent a RICalloSCT in order to identify prognostic factors that predict outcome. Eighty percent of patients had undergone a prior autologous stem cell transplantation and 25% had refractory disease at transplant. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 32 publications
11
135
2
4
Order By: Relevance
“…2A). Recently, many studies have mainly used reducedintensity conditioning for allogeneic HSCT, and most of these patients had previously undergone autologous HSCT [15][16][17]. Sureda et al compared the outcomes of allogeneic HSCT for patients with relapsed and refractory HL with myeloablative conditioning to those with reduced-intensity conditioning [18].…”
Section: Discussionmentioning
confidence: 99%
“…2A). Recently, many studies have mainly used reducedintensity conditioning for allogeneic HSCT, and most of these patients had previously undergone autologous HSCT [15][16][17]. Sureda et al compared the outcomes of allogeneic HSCT for patients with relapsed and refractory HL with myeloablative conditioning to those with reduced-intensity conditioning [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the reduced intensity conditioning regimen has shown a lower nonrelapse mortality making this a viable option for patients usually excluded from the conventional allo-SCT [32,33]. There are few published studies on the outcome of reduced intensity conditioning in diffuse large B-cell lymphoma or in aggressive lymphoma [34][35][36][37][38][39]. For patients with relapsed DLBCL, nonrelapse mortality rates with reduced intensity conditioning allogeneic transplantation, with few exceptions [36,40], have been surprisingly high (range 25-38%) [34,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Recently, Robinson et al investigated a population of 285 patients with affected HL who underwent RIC alloSCT and observed that both performance status and disease status at transplantation important clinical parameters for outcome. 29 The kinetics of disease recurrence were quite different in PET-positive patients: In patients with HL, disease progression usually was observed within the first 2 years after alloSCT; whereas most patients with aggressive NHL developed disease recurrence within the first 12 months, and then the curve reached a plateau. Although patients with positive pretransplantation PET scans had a dismal outcome, approximately 30% of them survived for a long period.…”
Section: Discussionmentioning
confidence: 99%